THE EFFECT OF LEADERSHIP STYLE ON QUALITY OF SERVICE THROUGH ORGANIZATIONAL CULTURE IN THE DEPARTMENT OF INVESTMENT, ESDM, AND TRANSMIGRATION OF GORONTALO PROVINCE - Abbas, Syahrawanty S.; Wantu, Sastro Mustapa (Universitas Negeri Gorontalo, 2022)
This research was conducted with the aim of analyzing the Influence of Leadership Style on Service Quality Through Organizational Culture in the Investment Office, ESDM and Transmigration of Gorontalo Province. This research uses descriptive type of quantitative approach by measuring the influence of the variable leadership style on service quality through organizational culture. The results showed that the leadership style variable showed a value of 3.092 with a significance value of 0.003 <0.05. The value of t table is 1,984. Thus, obtained t-count 3.092 > 1.984 which means that the hypothesis which states that leadership style has a positive and significant effect on service quality is accepted. The t-count value for the organizational culture variable shows the t-count value = 6.668 with a significance value of 0.000 <0.05. The value of t table is 1,984. Thus, obtained t-count (6.668) > t-table (1.984) which means that the hypothesis which states that organizational culture has a positive and significant influence on service quality can be accepted. The significance value of the leadership style variable on organizational culture is0.00<0.05 with a t-count value of 8.649 and t-table is1.984 or 8.649 > 1.98. This means that there is a significant influence of the leadership style variable on organizational culture.